(untitled) (Revista da EGN, 2023)
Fighting the COVID-19 pandemic in Brazil required actions from the Federal Government, through its Ministries and Local Authorities. The Armed Forces were called upon by the Ministry of Defense to act in Operation COVID-19, which began in March 2020. In total, 10 (ten) Joint Commands were created for the integrated use of the means of logistics, intelligence, and communications, in support to public health and safety agencies. In addition to these Joint Commands, the Aerospace Command, which is permanent, provided support to the other commands. The present work aimed to study the performance of the Armed Forces in confronting the COVID-19 pandemic, addressing issues related to interoperability, integration between civilians and military personnel, and impacts on the operation of the Armed Forces. The questionnaire was applied to Joint Commands members, both military and civilian. The study found that the Brazilian Armed Forces have a great capacity for mobilization, as evidenced by the numbers and diversity of the activities performed. The interoperability and relational capability of the military provided agility and integration in actions. However, suggestions and opportunities for improvement to increase the readiness of the Armed Forces and the State itself in similar situations were pointed out.